2012
DOI: 10.4049/jimmunol.1102736
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Fluid Induces Leukocyte Recruitment and Cytokine and Chemokine mRNA Expression in the Human Cervix after Coitus

Abstract: In mice, seminal fluid elicits an inflammation-like response in the female genital tract that activates immune adaptations to advance the likelihood of conception and pregnancy. In this study, we examined whether similar changes in leukocyte and cytokine parameters occur in the human cervix in response to the male partner’s seminal fluid. After a period of abstinence in proven-fertile women, duplicate sets of biopsies were taken from the ectocervix in the periovulatory period and again 48 h later, 12 h after u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
323
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(342 citation statements)
references
References 60 publications
17
323
2
Order By: Relevance
“…In addition to neutrophils a large number of antigen presenting cells (APCs) are recruited into the uterine endometrium, including macrophages and dendritic cells (DCs) expressing high levels of MHC class II [60,8]. This response has now been well characterised in other species including rabbit, horse, pig, and human [61][62][63][64]12].…”
Section: Post-insemination Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to neutrophils a large number of antigen presenting cells (APCs) are recruited into the uterine endometrium, including macrophages and dendritic cells (DCs) expressing high levels of MHC class II [60,8]. This response has now been well characterised in other species including rabbit, horse, pig, and human [61][62][63][64]12].…”
Section: Post-insemination Inflammationmentioning
confidence: 99%
“…This inflammatory response to semen and the associated change in the cytokine environment has been hypothesised to mediate several downstream effects in the female reproductive tract [9]. More recently these studies have been recapitulated in the human, particularly the cervix following intercourse [10][11][12]. Recently we have reported that pregnancies initiated in the absence of seminal plasma in mice give rise to progeny with altered metabolic profiles, obesity and hypertension due in part to perturbations in the peri-conceptional environment and oviduct expression of embryotrophic cytokines [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that semen deposition in the human female reproductive mucosa results in the induction of a strong inflammatory response that includes the production of inflammatory cytokines and chemokines (7,9,10), the upregulation of cyclooxygenase-2 expression (11), the infiltration of the cervix by neutrophils, and the recruitment of dendritic cells (DCs) (9,12,13). This inflammatory response induced by semen has also been described in mice, pigs, rabbits, and other mammals, and appears to induce the adaptation of the female immune response to promote fertility (14,15).…”
mentioning
confidence: 99%
“…The concentration of proteins in the seminal plasma ranges from 35 to 55 g/l, and proteomic analysis leads to the identification of .900 proteins (3,4). High levels of cytokines and chemokines have been described in seminal plasma, being the concentrations of TGF-b1, TGF-b2, TGFb3, IL-7, stromal cell-derived factor-1a, MCP-1, and IL-8 .1000 pg/ml (4)(5)(6)(7). Other cytokines and chemokines were detected at lower concentrations (∼50-200 pg/ml), among them, IL-1b, IL-5, IL-6, IL-13, IL-17, RANTES, MIP-1b, IFN-a, and G-CSF (4,6).…”
mentioning
confidence: 99%
“…At coitus, seminal fluid delivers male alloantigen, TGFβ and PGE2, causing recruitment and maturation of tolerogenic dendritic cells (DCs) into the uterine tissue, and driving further expansion of subsets of antigen-reactive Treg cells in the lymph nodes draining the uterus. In a recent study by Sharkey et al [15] it was demonstrated that seminal fluid introduced at intercourse elicits expression of proinflammatory cytokines and chemokines, and a robust recruitment of macrophages, dendritic cells, and memory T cells. They concluded that the leukocyte and cytokine environment induced in the cervix by seminal fluid appears competent to initiate adaptations in the female immune response that promote fertility.…”
Section: Discussionmentioning
confidence: 99%